The role of using linear programming in rationalizing production decisions - a case study of Madar Detergent Company in Lattakia Governorate- - السليمان نسرين; فداء الشيخ حسن (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research aims to show the importance of using the linear programming model in the process of rationalizing productive decisions, due to the great role that this model plays in making scientific and logical decisions to solve the problems faced by decision makers in companies, as this model helps the decision maker to choose the best alternative among the range of alternatives available to solve the problem facing him, which reflects positively on the company’s work, and to achieve this goal, the linear programming model was formulated and solved using Qm windows, the research found that the application of the linear programming model in madar detergent company has contributed to rationalizing production decisions, through the optimal use of available resources, and the optimal use of production capacity in the company under study, in addition to increasing the amount of production by (280.498) tons, and thus led to maximizing the company’s profitability by (208158924) s. p.